2020
DOI: 10.21307/ijssis-2020-027
|View full text |Cite
|
Sign up to set email alerts
|

Salt and sugar detection system using a compact microstrip patch antenna

Abstract: One of the reasons for many diseases such as diabetes, stroke, high blood pressure, kidney disease, etc., is the excess consumption of salt and sugar in the diet. So, to minimize these health problems, it is important to consume appropriate quantity of salt and sugar in the diet. This paper presents the design and development of a salt and sugar detection system using a low cost compact microstrip patch antenna. The salt and sugar detection system using a compact microstrip antenna is based upon the variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The shape of a wine glass has a smooth curvature along the length, so it becomes a traveling wave type of structure when implemented as an antenna. The variation in the width of the wine glass shape from the bottom toward its open end is responsible for its wide bandwidth 22‐24,30 . In addition, the slot is engraved in the antenna structure to increase the bandwidth of the antenna.…”
Section: Design Of the Antenna And 2d Woodpile Ebg Based Ground Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The shape of a wine glass has a smooth curvature along the length, so it becomes a traveling wave type of structure when implemented as an antenna. The variation in the width of the wine glass shape from the bottom toward its open end is responsible for its wide bandwidth 22‐24,30 . In addition, the slot is engraved in the antenna structure to increase the bandwidth of the antenna.…”
Section: Design Of the Antenna And 2d Woodpile Ebg Based Ground Surfacementioning
confidence: 99%
“…A compact, low‐profile microstrip antenna is presented for the detection of salt and sugar in water. The antenna uses DGS technology DGS technology for improving the antenna parameters and reducing the antenna size 24 …”
Section: Introductionmentioning
confidence: 99%
“…A crescent-shaped microstrip antenna-based sensor fabricated on FR-4 substrate was presented in [13]. In recent experimental study [14], a microstrip patch antenna employing a defective ground structure, which was implemented by on FR-4 substrate, demonstrated that it was able to detect different concentrations of salt and sugar in water. All of these antenna sensors mentioned above used rigid substrates typically deployed in electronic system applications.…”
Section: Determination Of Salinity and Sugar Concentration By Means Of A Circular-ring Monopole Textile Antenna-based Sensormentioning
confidence: 99%
“…The most serious limitations of microstrip antenna are its narrow bandwidth and poor gain (Balanis, 2005). Various techniques such as shorting post loading (Deshmukh et al, 2013;Kumar and Singh, 2011;Singh et al, 2010), gap-coupling (Kumar, 2014;Kumar and Singh, 2009;Mishra et al, 2019;Sharma, 2014), metamaterials (Yem and Lan, 2018), photonic band gap crystals (Sudha and Vedavathy, 2001), frequency selective surface (Yahya et al, 2018), defected ground structure (Ajay et al, 2019;Kumar and Masa-Campos, 2015;Kapoor et al, 2020;Njokweni and Kumar, 2020), etc., can be used to improve the antenna performance. Multiband antennas are required to be used for different bands applications.…”
mentioning
confidence: 99%